Efeito do nadar sobre o desempenho do pedal e corrida no triathlon super-sprint - Silva Neto, Luiz Vieira Da; Smirmaul, Bruno De Paula Caraça; Pignata, Bruno Henrique; Andries Junior, Orival (Universidade Estadual de Maringá, 2014)
The influence of the swimming sub-discipline upon the subsequent cycling/running performance seems to increase with the reduction of the triathlon's length. Thus, the purpose of this study was to analyze the effects of swimming upon the cycling and running performance during the super-sprint triathlon. Eight amateur triathletes performed a bout of super-sprint triathlon, consisting of swimming 375 m, cycling 10 km and running 2.5 km (Tri) and another bout consisting of only cycling 10 km and running 2.5 km (CR). Performing the swimming sub-discipline had a negative impact (p < 0.05) in the cycling performance (-8.4%) and total time (cycling + running; -5.4%) when compared to the performance achieved without the swimming sub-discipline. The running performance was not affected. Except running in CR protocol, all the other sub-disciplines presented high and significant correlations with the total time (r ≥ 0.84) for both protocols. In conclusion, performing the swimming sub-discipline has a negative impact in the subsequent cycling and total time (cycling + running) during the super-sprint triathlon.

A influência da sub-disciplina natação sobre o subsequente desempenho ciclismo/corrida parece aumentar com a redução da distância do triathlon. Assim, o objetivo do presente estudo foi analisar o efeito da natação sobre o desempenho do ciclismo e corrida no triathlon super-sprint. Oito triatletas amadores realizaram um teste de triathlon super-sprint, consistindo em nadar 375 m, pedalar 10 km e correr 2,5 km (Tri) e outro no qual deveriam apenas pedalar 10 km e correr 2,5 km (PC). A realização da sub-disciplina natação impactou de forma negativa o subsequente desempenho do ciclismo (-8,4%) e o tempo total (ciclismo + corrida; -5,4%) quando comparados à realização das mesmas sem a presença prévia da natação. Com exceção da corrida no protocolo PC, todas as sub-disciplinas apresentaram significativas correlações com o tempo total para ambos os protocolos. Em conclusão, a realização da sub-disciplina natação afeta negativamente o desempenho do pedal e do tempo total (pedal + corrida) durante o triathlon super-sprint.
Effect of swimming on the cycling and running performances during the super-sprint triathlon
Keywords: Triathlon; Residual Effect; Exercise Performance; Triathlon; Efeito Residual; Desempenho Esportivo